PERANCANGAN CONCEPT ART GAME “KATSVARI” - Prisma Simpati (Saraswati)
Concept art is one of the important elements that can not be separated in the production process. Various products and media today requires concept art as an alternative source of visual inspiration as a visual before the production process begins. Animated films and video games are some areas that need concept art as crucial factors in the pre-production process. The purpose of this study is creating concept art for "Katsvari" video game as an informal education that takes the theme of Indonesian endemic species that are increasingly endangered. Using the assimilation of geometric shapes with the distortion on the form of real endemic Indonesian animals to create a game characters that visually appealing. The steps taken during the process such as observations, literature study, data analysis, and study of the visual form. The result of this study is a concept art that contains a collection of two-dimensional illustration and alternative design for figures or character, and the location where the game takes place. Some aspects that can affecting a person interest of playing a game such as, visual aspect, gameplay, the storyline, and difficulty level of the game, regardless of any genre carried by the game. Visual aspect and storyline, can be summarized in a concept art that can be used as a collectible items for fans. This design is expected to be useful for the people or art community whom intend to explore the world of concept art of games and illustrations, as well as can be a good example to take Indonesian endemic animals as an inspiration to make an interesting game. Keywords : Concept Art, Game, Indonesian Endemic Animals, Video Game.